POTENTIAL OF TOURISM OBJECT PANORAMA BUKIK BULEK KENAGARIAN CANDUANG KOTO LAWEH KECAMATAN CANDUANG KABUPATEN AGAM - Veby Monica Sari; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose this reseach to determine the potential of: (1) tourist attractions, (2) accessibility, (3) amenities and (4) hospitality at the Panorama Bukik Bulek Kenagarian Canduang Koto Laweh, Canduang District, Agam Regency. This type of research is descriptive with a qualitative approach. To collect data done by observation, interviews and documentation. The data analysis technique used is a qualitative descriptive analysis technique with the process of data reduction analysis, data presentation, and drawing conclusions. The results of this study indicate that: 1) The potential of the tourist attraction of Bukik panorama in the form of natural attractions, this is evidenced by the reason visitors visit the tourist attraction because of the beautiful scenery from the height of the hill. 2) Accessibility to attractions is quite easy to find by visitors, but road conditions are not good and there is no public transportation. 3) At the tourist sites there are no supporting facilities such as restaurants and places of worship. 4) Hospitality or hospitality in welcoming visitors is very good, visitors linger in visiting tourist attractions, besides the environment around attractions is very safe from actions that unsettle visitors.